ANALISIS NILAI TAMBAH PENGOLAHAN NIRA AREN MENJADI GULA AREN DESA BULUH AWAR, KECAMATAN SIBOLANGIT - Posman HP Marpaung; Fandri Siburian (JURNAL REGIONOMIC, 2023)
This research took place in Buluh Awar Village, Sibolangit District, Deli Serdang Regency, North Sumatra Province. Determination of the research location was carried out by purposive sampling (intentionally), using the census method. Starting in the starting month in November 2021.Deli Serdang Regency is one of the centers for producing high quality palm sugar, a potential area for palm sugar processing businesses in North Sumatra Province, to be precise in Sibolangit District, Buluh Awar Village. Processing of palm sugar is carried out by the people of Buluh Awar Village with raw materials derived from palm plants that have begun to be cultivated. Sugar palm processing is intended to increase the added value of the raw material for the sap. These advantages include the added value of agro-industry by preserving agricultural products into processed products that are more durable and ready for consumption (Anonymous, 2010).This study aims to (1) analyze the type of added value and the value added from palm sap processing business into palm sugar in the research area. (2) analyze the availability of business inputs for processing palm sap into palm sugar in the study area. (3) knowing the business income of processing palm sap into palm sugar in the study area. (4) analyzing the feasibility of processing palm sap into palm sugar in the study area.The output of this internal research is the final report and is published in the online journal system (OJS) of Quality University Agrotechnoscience and additional outputs: Quality University local webinar.